Steps on a journey to TB control in Solomon Islands: a cross-sectional, mixed methods pre-post evaluation of a local language DVD. Issue 1 (December 2015) - Massey, Peter; Asugeni, Rowena; Wakageni, John; Kekeubata, Esau; Maena'aadi, John; Laete'esafi, John; Waneagea, Jackson; Asugeni, Vunivesi; MacLaren, David; Speare, Richard
Abstract Background In Solomon Islands many people with Tuberculosis (TB) have challenges in accessing services because of socio-cultural, geographic and health service reasons, resulting in delays in TB treatment and low detection rates. The purpose of this project was to (i) develop a local language audio-visual resource (DVD) about TB (ii) share this resource with people in remote villages and (iii) evaluate the process and outcomes. Methods The project involved the development and evaluation of a DVD in local Kwaio language. The DVD included five short videos based on the Australian Respiratory Council TB Education Flipchart. The DVD also included short videos of: traditional music/chanting (ai'imae); drama that presented an allegory of TB; and a short documentary on the redevelopment of the local TB Ward. A mixed-methods approach evaluated changes in TB knowledge and investigated the impact of the DVD. Results The DVD was recorded and produced in March–June 2013 and screened in 41 villages and hamlets. The pre-post DVD survey was completed by 64% (255/400) of people who viewed the DVD in the villages. Pre-DVD survey responses showed a moderate to high knowledge about TB signs, symptoms and treatment but 76/255 (30%) stated TB was caused by sorcery and 85/255 (33%) incorrectly stated that TB medication should be stopped when a patient feels better. The post-DVD survey showed a significant increase in people in coastal villages reporting (i) a 3-week cough would trigger a medical assessment and (ii) TB is mainly spread through the air. Statements that TB is not caused by sorcery increased post-DVD in both coastal and mountain villages, however belief in sorcery in mountain villages remained high at 20/70 (29%). Conclusions The local DVD resource was developed within local cultural understandings and oral traditions of Kwaio people. Using modern but accessible DVD technology generated a lot of interest about the disease and the stories. The project evaluation indicates that current delays in seeking treatment may be more due to socio-cultural and health service factors than awareness of the disease. Therefore the development of TB services, including TB education, which are culturally sensitive, remains important.